AI-Driven Personalized Learning and Its Ethical Implications for Educational Counseling - Khusnadin, Muhammad Hafidz; Hariyanti , Mustika; Kadir, Abdul (Yayasan Minang Darussalam, 2024)
In the contemporary digital landscape, AI-driven personalized learning has emerged as a transformative approach to enhancing educational experiences. This article examines the integration of artificial intelligence within educational settings, focusing specifically on its implications for educational counseling. By leveraging sophisticated data analytics, AI systems can customize learning materials and instructional strategies to align with the unique needs and preferences of individual learners. This tailored approach not only aims to improve academic outcomes but also fosters greater engagement and motivation among students. However, the deployment of AI in education raises significant ethical considerations. Issues such as data privacy, where sensitive student information may be compromised, and algorithmic bias, which can perpetuate inequities in learning opportunities. This research highlights both the potential benefits and inherent risks associated with AI-driven personalized learning. It advocates for a balanced perspective that emphasizes ethical practices in the implementation of technology in education. Recommendations for educational counselors include fostering digital literacy, advocating for transparent data practices, and actively participating in discussions about the ethical use of AI in educational contexts.